Synthesis, characterization, and efficacy of antituberculosis isoniazid zinc aluminum-layered double hydroxide based nanocomposites - Saifullah B (Dove Medical Press, 2016)
Bullo Saifullah,1 Mohamed Ezzat El Zowalaty,2,3 Palanisamy Arulselvan,3 Sharida Fakurazi,3,4 Thomas J Webster,5–7 Benjamin Mahler Geilich,5,6 Mohd Zobir Hussein1 1Materials Synthesis and Characterization Laboratory, Institute of Advanced Technology, (ITMA), Universiti Putra Malaysia, Serdang, Selangor, Malaysia; 2School of Health Sciences, University of KwaZulu-Natal, Westville Campus, Durban, South Africa; 3Laboratory of Vaccines and Immunotherapeutics, Institute of Bioscience, 4Department of Human Anatomy, Faculty of Medicine and Health Science, Universiti Putra Malaysia, Serdang, Selangor, Malaysia; 5Department of Chemical Engineering, 6Department of Bioengineering, Northeastern University, Boston, MA, USA; 7Center of Excellence for Advanced Materials Research, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: The chemotherapy for tuberculosis (TB) is complicated by its long-term treatment, its frequent drug dosing, and the adverse effects of anti-TB drugs. In this study, we have developed two nanocomposites (A and B) by intercalating the anti-TB drug isoniazid (INH) into Zn/Al-layered double hydroxides. The average size of the nanocomposites was found to be ~164 nm. The efficacy of the Zn/Al-layered double hydroxides intercalated INH against Mycobacterium tuberculosis was increased by approximately three times more than free INH. The nanocomposites were also found to be active against Gram-positive and -negative bacteria. Compared to the free INH, the nanodelivery formulation was determined to be three times more biocompatible with human normal lung fibroblast MRC-5 cells and 3T3 fibroblast cells at a very high concentration of 50 µg/mL for up to 72 hours. The in vitro release of INH from the Zn/Al-layered double hydroxides was found to be sustained in human body-simulated buffer solutions of pH 4.8 and 7.4. This research is a step forward in making the TB chemotherapy patient friendly. Keywords: tuberculosis, Zn/Al-LDHs, drug delivery, biomaterial, antimicrobial, activity, sustained release formulation, nanomedicine